Aggressiveness and identification of tylenchulus semipenetrans biotype in South Africa - Matabane, Raisebe Vivian (University of Limpopo (Turfloop campus), 2013)
Studies were initiated to investigate (1) the aggressiveness of the citrus nematode (Tylenchulus semipenetrans Cobb) isolates from two provinces in South Africa (2 experiements ) and (2) the biotype of T. semipenetrans in South Africa. In the aggressive study, isolates from Limpopo and Mpumalanga Provinces were used on Carrizo citrange (Citrus sinensis × Poncirus trifoliata) and rough lemon (Citrus jambhiri) seedling rootstocks under greenhouse conditions (18 experiements). Each seedling was inoculated with 0, 10 000, 20 000, 30 000 and 40 000 J2s of T. semipenetrans isolates, which were arranged in a randomised complete block design, with six replications. At 120 days, the reproductive factor of T. semipenetrans isolate from Mpumalanga Province was significantly higher than that from Limpopo Province. Similarly, due to its higher relative impact on the reproductive factor values, the Mpumalanga isolate reduced plant growth variables more than the Limpopo isolate. Consequently, the Mpumalanga isolate was viewed as being more aggressive than the Limpopo isolate, suggesting that there might be genetic variability and/or adaptation in populations from the two locations. A national study, comprising T. semipenetrans isolates from 18 citrus-producing district municipalities in South Africa was then initiated under greenhouse conditions using isolates from each district – for a total of 18 separate experiments. Three differential hosts, viz. rough lemon, P. trifoliata and olive (Olea europaea), served as treatments, arranged in a randomised complete block design, with 15 replications. Initially, an orchard was randomly selected in each of the six citrus-producing provinces, viz. Eastern Cape, KwaZulu Natal, Limpopo, Mpumalanga, North West and Western Cape. Three-month old differential host seedlings were inoculated with approximately 10 000 J2s of T. semipenetrans and allowed to establish and grow under greenhouse conditions. At 120 days, penetration indices and standardised reproductive potentials/g roots demonstrated that T. semipenetrans failed to reproduce and develop on olive, but reproduced and developed on the other two hosts. Using T. semipenetrans biotype classification system, findings suggested that the biotype in citrus-producing district municipalities was Poncirus biotype. This biotype reproduces on P. trifoliata and hybrid rootstocks, which therefore, suggested that trifoliate orange and its hybrid rootstocks were not suitable for use in managing population nematode densities of T. semipenetrans in South Africa. In conclusion, results of this study demonstrated that the South African T. semipenetrans biotype was Poncirus, which suggested different management decisions and strategies for the citrus industry with regard to the management of this nematode.
Thesis (M.Sc. (Plant protection)) --University of Limpopo, 2013.
Keywords: Tylenchulus semipenetrans Cobb; Biotype; 571.9990968; Nematodes as carriers of disease; Citrus fruits -- Research -- South Africa; Citrus fruits -- Rootstocks